Red Man Syndrome Following Intraperitoneal Vancomycin in a Child with Peritonitis - Domis, Melissa J.; Moritz, Michael L. (Frontiers in Pediatrics, 2014)
Red Man Syndrome has frequently been reported to occur with intravenous vancomycin therapy. However, there have been few reports of this complication during intraperitoneal treatment with vancomycin. This report describes an 11-year-old boy with end stage renal disease who developed Red Man Syndrome 45 minutes into the initial loading dose of intraperitoneal vancomycin for the treatment of bacterial peritonitis with a vancomycin level of 38.8 mcg/mL. The patient developed this adverse reaction despite appropriate initial loading dose per ISPD guidelines for continuous treatment (1000 mg/L). This case emphasizes the importance of monitoring for adverse reactions of vancomycin therapy, and raises dosing considerations that differ slightly from the currently recommended ISPD guidelines for intraperitoneal vancomycin treatment in the treatment of bacterial peritonitis.